Supply or demand: What drives fluctuations in the bank loan market? - Carlo Altavilla; Miguel Boucinha; Paul Bouscasse (European Central Bank (ECB), 2022)
We propose a new methodology to identify aggregate demand and supply shocks in the bank loan market. We present a model of sticky bank-firm relationships, estimate its structural parameters in euro area credit register data, and infer aggregate shocks based on those estimates. To achieve credible identification, we leverage banks' exposure to various sectors' heterogeneous liquidity needs during the COVID-19 Pandemic. We find that developments in lending volumes following the pandemic were largely explained by demand shocks. Fluctuations in lending rates were instead mostly determined by bank- driven supply shocks and borrower risk. A by-product of our analysis is a structural interpretation of two-way fixed effects regressions in loan-level data: according to our framework, firm- and bank-time fixed effects only separate demand from supply under certain parametric assumptions. In the data, the conditions are satisfied for supply but not for demand: bank-time fixed effects identify true supply shocks up to a time constant, while firm-time fixed effects are contaminated by supply forces. Our methodology overcomes this limitation: we identify supply and demand shocks at the aggregate and individual levels.
Keywords: E51; G21; G32; 330; credit demand; credit supply